Amir-Moezzi - Mohammad Ali - Jean Daniel Dubois - Christelle Jullien - Florence Jullien (eds.): Pensée grecque et sagesse d’Orient. Hommage à Michel Tardieu - Bausi, Alessandro (Aethiopica, 2010)
Review